95.1k views
4 votes
Solve by substitution.2x + y = -9(3x + 5y = 4([?],[])

Solve by substitution.2x + y = -9(3x + 5y = 4([?],[])-example-1

1 Answer

6 votes

The given system is


\mleft\{\begin{aligned}2x+y=-9 \\ 3x+5y=4\end{aligned}\mright.

Let's isolate y in the first equation.


\begin{gathered} 2x+y=-9 \\ y=-9-2x \end{gathered}

Then, we replace the equation we've got in the second equation of the system.


3x+5(-9-2x)=4

Now, we solve for x.


\begin{gathered} 3x-45-10x=4 \\ -7x=4+45 \\ -7x=49 \\ x=(49)/(-7) \\ x=-7 \end{gathered}

We use this value to find y.


\begin{gathered} y=-9-2(-7) \\ y=-9+14 \\ y=5 \end{gathered}

Therefore, the solutions are x = -7 and y = 5.

User KGhatak
by
5.3k points